Education Policy and Intergenerational Transfers in Equilibrium - Abbott, Brant; Gallipoli, Giovanni; Meghir, Costas; Violante, Giovanni L. (Journal of Political Economy, 2019)
We examine the equilibrium effects of college financial aid policies building an overlapping-generations life cycle model with education, labor supply, and saving decisions. Cognitive and noncognitive skills of children depend on parental education and skills and affect education and labor market outcomes. Education is funded by parental transfers that supplement grants, loans, and student labor supply. Crowding out of parental transfers by government programs is sizable and cannot be ignored. The current system of federal aid improves long-run welfare by 6 percent. More generous ability-tested grants would increase welfare and dominate both an expansion of student loans and a labor tax cut.